Thermal, structural and electrical properties of Li2BaSiO4 ceramic electrolyte - Adnan, Syed Bahari Ramadzan Syed; Mohamed, Nor Sabirin; Mustaffa, Nur Amalina; Zainal, Norazlin; Ibrahim, Suriani; Radzi, Z.I. (Elsevier, 2019)
Lithium Barium Silicate (Li2BaSiO4) solid electrolyte was prepared by Sol - gel method with citric acid as the chelating agent. Thermal, structural and electrical characterization was done using Thermogravimetric/Differential Scanning Calorimetry, X-ray Diffraction, Fourier Transform Infrared and Impedance Spectroscopy respectively. Pure phase of Li2BaSiO4 sintered at 700 °C and 800 °C showed stability at that temperature. The conductivity of the electrolyte increased linearly with temperature. The bulk conductivity of the samples sintered at 800 °C was found to be 1.45 × 10−4 S cm−1 at 500 °C. The temperature dependence also follows the Arrhenius relation with activation energy of 0.11 eV. The complex impedance analysis of the electrolyte showed a typical negative temperature coefficient of resistance (NTCR) behavior.